Characterization of South Asian Agricultural Residues for Potential Utilization in Future 'energy mix'. (August 2015) - Danish, Muhammad; Naqvi, Muhammad; Farooq, Usman; Naqvi, Salman
Abstract: This paper characterizes various locally available agricultural residues in South Asian region to evaluate their potential as feedstock for renewable energy production and contributing toward solving energy crisis and environmental issues. The thermo-chemical characterization has been performed in order to determine if the residues have potential to be used in biomass conversion technologies producing combined heat and power. The characterization methods for comparing different agricultural residues include proximate and ultimate analysis, heating value, ash content, thermo gravimetric analysis (TGA) and structural composition analysis (SCA). Widely available agricultural wastes in South Asian region were selected for the characterization i.e. bagasse, almond shell, corn cob, cotton stalks, wheat straw, sawdust, corn leaf, rice husk, rice straw, and corn straw. The analysis showed that the corn cob had the highest moisture content that will result in low energy efficiency of the thermal conversion technology due to energy requirement for drying. Whereas almond shell had the lowest moisture content. Ash and volatile contents were found to be highest in rice straw and almond shell respectively. The thermo gravimetric analysis showed that most of the agricultural residues can be easily decomposed and represent potential feedstock for biomass flexible combined heat and power systems through pyrolysis or gasification.